Th1rteen r3asons why : a novel - Asher, Jay (New York Razorbill, 2010)
When high school student Clay Jenkins receives a box in the mail containing thirteen cassette tapes recorded by his classmate Hannah, who committed suicide, he spends a bewildering and heartbreaking night crisscrossing their town, listening to Hannah's voice recounting the events leading up to her death